Change agents: The impact of a student partnership on the educational practice of a diverse higher education engineering faculty - Knight, Gillian; Ordidge, Helen; Timothy, Adam; Davis, Matthew (International Journal for Students as Partners, 2022)
This article describes the implementation of a new student partnership across a large and diverse STEM faculty and the impact this four-year partnership had on enhancing students’ experience. This innovative partnership recruited and employed students, termed student experience champions (SEC), to inform and develop inclusive educational initiatives in response to their educational experiences. This partnership enabled the faculty to develop a dynamic and agile working relationship with their students, creating an environment where students informed the strategic direction of the student experience and leading faculty and departmental educational projects that resulted in institutional changes. The breadth of the SEC projects enabled the benefits of student partnerships to be appreciated across the faculty, leading to a culture change where SEC are now viewed as partners in programme enhancement.